2023
DOI: 10.1097/jcn.0000000000000999
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Study of Social Determinants and Self-care in Adults With Heart Failure

Abstract: Background The burden of heart failure (HF) is unequally distributed among population groups. Few study authors have described social determinants of health (SDoH) enabling/impeding self-care. Aim The aim of this study was to explore the relationship between SDoH and self-care in patients with HF. Methods Using a convergent mixed-methods design, we assessed SDoH and self-care in 104 patients with HF using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…27,28 The patients also discussed the importance of both family and peer social support; similar to other research, they indicated how critical family support was but how social support networks were often lacking. 27,28 The patients and caregiver felt that virtual support groups or recordings of other patients should be leveraged to build comradery, provide an opportunity to ask questions, and learn about others' experiences with HF. The patients and caregiver also spent much of the conversation discussing the challenges in managing dietary restrictions, both for HF but also in tandem with those of other chronic conditions.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…27,28 The patients also discussed the importance of both family and peer social support; similar to other research, they indicated how critical family support was but how social support networks were often lacking. 27,28 The patients and caregiver felt that virtual support groups or recordings of other patients should be leveraged to build comradery, provide an opportunity to ask questions, and learn about others' experiences with HF. The patients and caregiver also spent much of the conversation discussing the challenges in managing dietary restrictions, both for HF but also in tandem with those of other chronic conditions.…”
Section: Discussionsupporting
confidence: 56%
“…The patients also discussed how important it was for them to regain their independence and quality of life, but as a motivator to GDMT uptake. Other research has noted that patients with HF and family members often struggle with poor quality of life and that patients have a difficult time with the loss of independence and need to rely on others 27,28 . The patients also discussed the importance of both family and peer social support; similar to other research, they indicated how critical family support was but how social support networks were often lacking 27,28 .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations